Islamic Hedging in the Perspective of Maqasid Shariah ‘Abd al-Majid al-Najjar - Ahmad Syaichoni; Amalia Nuril Hidayati (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 21 Issue 2 Page (150-161)